Self employability of Malaysian public higher education institution graduates nationwide / Tan Chee Hian, Tham Yin Choong and Rahim Md Sail - Tham, Yin Choong; Md Sail, Rahim (Faculty of Sports Science and Recreation, 2014)
This study was mainly to investigate the level or readiness which consisted variable like personal attributes and personal quality of PHEI graduates' perception on their employability. In order to justify the objectives in elaborating this dimension in the overall Graduates Employability Questionnaire (GEQ, 2010) was adopted and the result showed every dimension of the GEQ with a) level of employment circumstances/learning was with mean score of 3.35; b) level of selfattitude towards responsibility which statement of self willingness to take up responsibility without interference of third part as well as other characteristic showed mean score of 3.89; and c) level of soft skills in work life showed significant mean score of 3.99. As far as determination of relationship or between selected factors and the employability of these graduate were concerned, statistically graduates' personal readiness factor was positive, moderate correlation with the employability of graduates (r = .500, N = 184, p < .05); Guilford's rule of Thumb was applied indicating supportive that personal readiness of graduates could influence the employability of one; the correlation between personal attributes and personal qualities also showed contributive results (r = .608, N = 184, p < .05 and r = .428, N = 184, p <.05) respectively. This concluded that personal readiness of PHEI graduates should highly emphasize on constructional proficiency programme in the university delivery system especially for undergraduate programme concerned.